INTERCONNECTION BETWEEN THE HEART AND LUNGS: PATHOPHYSIOLOGICAL PERSPECTIVES - Temirova Dilnoza Valiyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The heart and lungs function in close coordination to maintain oxygenation and circulation. Any dysfunction in one organ significantly impacts the other, leading to conditions such as pulmonary hypertension, cor pulmonale, and heart failure. This article explores the physiological and pathophysiological interactions between the heart and lungs, highlighting the clinical implications of their interdependence.